Virtual Prototyping-Based Development of Stepper Motor Design - Konstantin Kamberov; Georgi Todorov; Blagovest Zlatev (Actuators)
This study presents a methodology used in the design development of stepper motors. The methodology unites virtual and physical techniques to assess the structure under development at its various design stages. Virtual prototyping is used twice, at the concept and early design stages. Concept check aims to give more general directions for further design development. In contrast, the simulations at the detailed design stage allow for assessing various design parameters at a high level of confidence. The testing of a physical prototype is used to validate simulation results. It is also used to check the design just before it is finished. The presented methodology is demonstrated in an industrial use case for stepper motor development for hydraulic valve application. The main contribution of this study is related to the way the combination of virtual and physical prototyping and testing at different product development stages applies to the development of stepper motors and other similar products.